UJI AKTIVITAS ANTIBAKTERI EKSTRAK KENCUR (Kaempferia galanga L.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus dan Streptococcus viridans - Akhmad Haerazi; Dwi Soelistya Dyah Jekti; Yayuk Andayani (Bioscientist : Jurnal Ilmiah Biologi, 2014)
Research on the Activity of Antibacterial Extract of Kencur (Kaempferia galanga L.) on Growth of Staphylococcus aureus and Streptococcus viridans In Vitro has been done. The aim of this research was to know the antibacterial activity of Kencur extract (Kaempferia galanga L.) on the growth of Staphylococcus aureus and Streptococcus viridans bacteria and to know MIC and MBC values were done by dilution method on MHB media. The main ingredients used in this study were dried kencur rhizome extracted by using ethanol solvent. The kencur extract from the extraction result was then tested for antibacterial activity on Staphylococcus aureus and Streptococcus viridans with the concentrations used were 30%, 40%, 50%, 60% and 70%. The results showed that kempur extract (Kaempferia galanga L.) at 70% concentration had antimicrobial activity against Staphylococcus aureus of 15 mm and Streptococcus viridans of 16 mm. MIC tests on the growth of Staphylococcus aureus and Streptococcus viridans bacteria were at concentrations of 38% and MBC on growth of Staphylococcus aureus and Streptococcus viridans bacteria was at concentrations of 40%.